An integrated analysis of housing and transit affordability in the Chicago metropolitan area. Issue 2 (4th March 2021) - Liu, Dong; Kwan, Mei‐Po; Kan, Zihan; Song, Yimeng
Abstract : An integrated analysis of housing and transport affordability provides comprehensive insights into the affordability of different locations in a city. By focusing on transit‐based workers, who constitute a significant portion of commuters but are understudied in the affordability literature, this study proposes a new, integrated method for estimating housing and transit (H + T) affordability in the Chicago Metropolitan Area using census data and data from the Google Maps Directions API. Methodologically, the study contributes to the literature by proposing and implementing a new method that estimates H + T affordability in an integrated manner based on census data and data from the Google Maps Directions API across three types of housing occupants (i.e., owners with/without a mortgage and renters). Empirically, the results indicate varying H + T affordability distribution patterns among different types of housing occupants and provide a comprehensive picture of housing and transport affordability in the study area without incurring prohibitive time and cost of data collection. The study indicates that policy‐makers should consider expanding the existing concessionary fare scheme to include low‐income residents and establishing affordable housing programmes that subsidise not only mortgage/rent but also miscellaneous costs related to housing (such as utilities) in order to improve the overall H + T affordability for different types of housing occupants. Abstract : This study proposes a new data‐driven method for measuring housing and transit (H + T) affordability. The geographic patterns of H + T affordability vary significantly depending on the type of housing occupants (i.e., owners with/without a mortgage and renters). Suburban neighborhoods have higher H + T affordability than their central city counterparts.